2012
DOI: 10.1007/s12011-012-9385-x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Dietary Garcinia cambogia Extract on Serum Essential Minerals (Calcium, Phosphorus, Magnesium) and Trace Elements (Iron, Copper, Zinc) in Rats Fed with High-Lipid Diet

Abstract: The aim of the study was to investigate the effect of Garcinia cambogia extract on serum calcium (Ca), phosphorus (P), magnesium (Mg), iron (Fe), zinc (Zn) and copper (Cu) concentrations in rats fed with the normal or the high-lipid and -cholesterol diet. Thirty 1-year-old female Sprague-Dawley rats (pathogen-free), weighing an average of 229 g, were randomly assigned to three experimental groups of ten animals each. Diets and tap water were given ad libitum for 75 days. Group 1 (control group) was fed with ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 30 publications
0
7
0
1
Order By: Relevance
“…Many studies had found that (-)-HCA administration reduces fat accumulation in chickens [59, 60], rodents [32, 61, 62] and humans [51, 63]. Excess accumulation of lipids results in oxidative stress, mitochondrial dysfunction and obesity [64].…”
Section: Discussionmentioning
confidence: 99%
“…Many studies had found that (-)-HCA administration reduces fat accumulation in chickens [59, 60], rodents [32, 61, 62] and humans [51, 63]. Excess accumulation of lipids results in oxidative stress, mitochondrial dysfunction and obesity [64].…”
Section: Discussionmentioning
confidence: 99%
“…[112113] The fruits, which are the most important part, resemble a miniature pumpkin and are used as an acidulant in the curries and to prepare sherbat. Its main component is hydroxycitric acid (HCA), which is an inhibitor of adenosine triphosphate (ATP) citrate lyase that reduces the biosynthesis of fatty acid and thus aids in weight reduction.…”
Section: Spices With Anti-ibd Effectsmentioning
confidence: 99%
“…24 However, recent studies have raised concerns about Mn toxicity such as cytotoxicity and neurotoxicity. [29][30][31] The Zn cation acts as a mediated inhibitor of neurotrophins and can even lead to cell death, 32 and Zn accumulation in the human body may induce embryonic motor neuron death and affect mature motor neurons. It was also found that the neurotoxicity of Mn presented as an induction factor for a disease with similar properties to Parkinson's disease.…”
Section: Introductionmentioning
confidence: 99%